Pediatric hyperimmunoglobulin E syndrome: A case series of 4 children in China. Issue 14 (April 2018) - Fan, Huifeng; Huang, Li; Yang, Diyuan; Lin, Yunting; Lu, Gen; Xie, Yaping; Yu, Jialu; Zhang, Dongwei
Abstract : Abstract: Hyperimmunoglobulin E syndromes (HIES) are rare primary immunodeficiency diseases characterized by markedly elevated serum immunoglobulin (Ig) E, recurrent pneumonia, and chronic eczema. To date, information about pediatric HIES is limited. We aimed to evaluate the spectrum of clinical and immunological features in pediatric patients with HIES in China. We retrospectively reviewed the cases of 4 pediatric patients with HIES followed at the Guangzhou Women and Children's Medical Center from May 2013 to September 2017. We analyzed clinical presentation, laboratory data, immunological evaluations, imagenological characteristics, treatment, response to therapy, genetic and bronchoalveolar lavage fluid (BALF) findings, and prognosis. The common clinical features of the patients were recurrent respiratory and mucocutaneous infections and eczematoid skin lesions. In 3 of 4 patients, BALF and transbronchial lung biopsy (TBLB) demonstrated fungal pneumonia with organisms including invasive Aspergillus and Penicillium marneffei . Elevated serum IgG and IgM were detected in 3 and 2 cases, respectively, while CD4+ T and CD19+ B cells were slightly reduced in only 1 patient. Nitroblue tetrazolium tests (NBTs) were normal in all patients, and reduced natural killer cell counts were identified in 3 patients. A novel missense mutation in exon 17 (c.1593A>T, p.K531N) was identified in the signal transducer and activator of transcription 3 ( STAT3 ) gene that has not been reported previously. One patient had 3 homozygous nonsynonymous variations of the complement receptor 2 ( CR2 ) gene distributed in exons 10 (c.1916G>A, p.S639N) and 11 (c.1987T>C, p.S663P and c.2012G>A, p.R671H) with high frequency. This case series suggests that fungi are important respiratory pathogens in children with HIES and should be considered in cases of pneumonia in this population. The NIH scoring system does not allow diagnostic certainty, particularly in infants, because some of the common manifestations of HIES may not develop until the patient matures. Pulmonary complications must be identified in the early stage of the disease to treat them effectively. In addition, we report a mutation in STAT3 that has not been identified previously.